Complementary molecular approaches reveal heterogeneous CDH1 germline defects in Italian patients with hereditary diffuse gastric cancer (HDGC) syndrome. Issue 5 (3rd February 2014) - Molinaro, Valeria; Pensotti, Valeria; Marabelli, Monica; Feroce, Irene; Barile, Monica; Pozzi, Simonetta; Laghi, Luigi; Serrano, Davide; Bernard, Loris; Bonanni, Bernardo; Ranzani, Guglielmina Nadia
<x xml:space="preserve">Abstract</x> Germline inactivation of the E‐cadherin gene (CDH1) is associated with hereditary diffuse gastric cancer (HDGC), a rare autosomal dominant syndrome predisposing to both diffuse gastric cancer (DGC) and lobular breast cancer (LBC). We searched for CDH1 germline defects in 32 HDGC Italian probands selected according to international consensus criteria and in 5 selected relatives. We used a series of molecular methods, including: DNA sequencing, multiplex ligation‐dependent probe amplification, single‐nucleotide primer extension, bisulfite sequencing, reverse‐transcription PCR, and bioinformatics tools. We identified pathogenic mutations in 6 out of 32 probands (19%): one truncating and two missense mutations, one large deletion, one allelic expression imbalance and one splicing defect. Three out of six CDH1 constitutive alterations were novel. Our data support the need for a multimethod approach for CDH1 genetic testing, demonstrating that both DNA and RNA analyses are required to increase the detection rate of pathogenic mutations, thus reducing the number of patients without a clear molecular diagnosis. On the whole, our results indicate that not only DGC patients, but also subjects with personal or family history of LBC might benefit from CDH1 genetic testing. Moreover, our findings support the notion that prophylactic gastrectomy should be offered to asymptomatic CDH1 mutation carriers; indeed, while endoscopic analysis with histological examination of random gastric biopsies can miss cancer foci, gastrectomy performed in these subjects always revealed foci of cancer cells. © 2014 Wiley Periodicals, Inc.